Case report: Complex evaluation of coagulation, fibrinolysis and inflammatory cytokines in a SARS-CoV-2 infected pregnant woman with fetal loss - Tóth, Eszter Lilla; Orbán-Kálmándi, Rita; Bagoly, Zsuzsa; Lóczi, Linda; Deli, Tamás; Török, Olga; Molnár, Sarolta; Baráth, Sándor; Singh, Parvind; Hevessy, Zsuzsanna; Katona, Éva; Fagyas, Miklós; et al. (Frontiers in Immunology, 2024)
Background: SARS-CoV-2 infection during pregnancy increases the risk of severe obstetrical complications. Detailed evaluation of COVID-19-associated coagulopathy in a pregnancy with stillbirth hasn't been described so far. Besides knowledge gaps in the pathomechanism leading to stillbirth in COVID-19 pregnancies, currently, no prognostic biomarker is available to identify pregnant patients who are at imminent risk of COVID-19-associated maternal and fetal complications, requiring immediate medical attention. Case: Here we report the case of a 28-year-old SARS-CoV-2 infected pregnant patient, admitted to our hospital at 28 weeks of gestation with intrauterine fetal loss. The presence of SARS-CoV-2 placentitis was confirmed by immunohistological evaluation of the placenta. She had only mild upper respiratory symptoms and her vital signs were within reference throughout labour and postpartum. The stillborn infant was delivered per vias naturales. Fibrinogen concentrate was administered before and after labour due to markedly decreased fibrinogen levels (1.49 g/l) at admission and excessive bleeding during and after delivery. Although coagulation screening tests were not alarming at admission, the balance of hemostasis was strikingly distorted in the patient. As compared to healthy age-and gestational age-matched pregnant controls, increased D-dimer, low FVIII activity, low FXIII level, marked hypocoagulability as demonstrated by the thrombin generation assay, together with shortened clotlysis and decreased levels of fibrinolytic proteins were observed. These alterations most likely have contributed to the increased bleeding observed during labour and in the early postpartum period. Interestingly, at the same time, only moderately altered inflammatory cytokine levels were found at admission. Serum ACE2 activity did not differ in the patient from that of age-and gestational agematched healthy controls, suggesting that despite previous speculations in the literature, ACE2 may not be used as a potential biomarker for the prediction of COVID-19 placentitis and threatening fetal loss in SARS-CoV-2-infected pregnancies. Conclusions: Although based on this case report no prognostic biomarker could be identified for use in pregnant patients with imminent risk of fetal loss associated with COVID-19 placentitis, the abovedescribed hemostasis alterations warrant awareness of postpartum hemorrhagic complications and could be helpful to identify patients requiring intensified medical attention.